Синтез и исследование нанопорошков ферромолибдата стронция с высокой степенью сверхструктурного упорядочения для спинтроники - Ярмолич, М.В.; Каланда, Н.А.; Демьянов, С.Е.; Силибин, М.В.; Горох, Г.Г. (Технология и конструирование в электронной аппаратуре, 2016)
Наноразмерная магнитная керамика со структурой двойного перовскита на основе соединений ферромолибдата стронция (ФМС) Sr₂FeMoO₆₋δ синтезирована цитрат-гель-методом из консистентных растворов с различным значением pH. Установлена корреляционная зависимость скорости и степени фазовых превращений ФМС в результате высокотемпературного отжига. Показано, что на магнитное состояние керамики влияет микроструктура порошка ФМС и степень сверхструктурного упорядочения катионов Fe³⁺, Mo⁵⁺, которая существенным образом зависит от величины pH исходных растворов. Установлено, что при pH = 4 образуются наночастицы с большей микроструктурной и магнитной однородностью, а также меньшей магнитной анизотропией. Определены оптимальные условия синтеза нанопорошков ФМС, позволяющие осуществлять направленное изменение фазового состава синтезируемой наноразмерной керамики с воспроизводимыми физико-химическими свойствами. Нанорозмірну магнітну кераміку зі структурою подвійного перовскіту на основі сполук ферромолібдату стронцію (ФМС) Sr₂FeMoO₆₋δ синтезовано цитрат-гель-методом з сумісних розчинів з різним значенням pH. Встановлено кореляційну залежність швидкості і ступеня фазових перетворень ФМС внаслідок високотемпературного відпалу. Показано, що на магнітний стан кераміки впливає мікроструктура порошку ФМС і ступінь надструктурного впорядкування катіонів Fe³⁺, Mo⁵⁺, яка істотно залежить від pH вихідного розчину. Встановлено, що при меншій величині pH утворюються наночастинки з більшою мікроструктурною і магнітною однорідністю, а також меншою магнітною анізотропією. Визначено оптимальні умови синтезу нанопорошків ФМС, що дозволяють здійснювати спрямовану зміну фазового складу синтезованої нанорозмірної кераміки з відтворюваними фізико-хімічними властивостями. The metal oxide compounds Sr₂FeMoO₆₋δ systems with an ordered double perovskite structure due to their unique and extremely important magnetotransport and magnetic properties are among the most promising materials for spintronic devices. In the present work, we investigated the correlation between the citrate-gel synthesis conditions (pH of initial solutions and annealing temperature) and the microstructure, phase transformations and magnetic properties of the Sr₂FeMoO₆₋δ nanopowders. According to the results the average grain size of the powders in the dispersion grows from 250 to 550 nm with increasing of pH values. Single-phase nanosized Sr₂FeMoO₆₋δ powders had various degrees of superstructural ordering of Fe³⁺ and Mo⁵⁺ (P = 65% for pH = 4, P = 51% for pH = 6 and P = 20 % for pH = 9). With increasing of pH, the Fe²⁺ concentration increases from 63% to 72%, and the Fe⁺³ concentration drops from 37% to 28%. According to the results of investigations of magnetization temperature dependence in Sr₂FeMoO₆₋δ powders a metastable superparamagnetic state was established at TS<19 K in low-dimensional grains. An optimized synthesis procedure, based on an initial solution of pH = 4, has allowed obtaining a single-phase Sr₂FeMoO₆₋δ compound having grain size in the range of 50-120 nm and a superstructural ordering of iron and molybdenum cations of 88%. The optimum conditions of synthesis of nanopowders strontium ferromolybdate allow for the directional change of the phase composition of the synthesized nanosized ceramic with reproducible physical and chemical properties.